Particle size determines the distribution of chemical composition and antibiotic resistance genes in urban atmospheric bioaerosols - Habeebrahuman, Haajira Beevi; Qian, Youfen; Shrivastava, Vibhaw; Rafeeq, Shamil; Dikmen, Emre; Sagirli, Eda; Lang-Yona, Naama (Elsevier, 2026)
Airborne aerosols impact urban air quality and public health through transport and inhalation of chemical pollutants and microbial agents, including antibiotic-resistant bacteria. However, relationships between particle size, environmental parameters, chemical and microbial composition, and antibiotic-resistance dispersion remain poorly understood. This study examined the interplay between these parameters for size-segregated airborne particles collected in a mid-sized urban area. Fine particles (<1.5 m) contained elevated K+, NH4+, Cl-, and anthropogenic carbonaceous compounds, with predominant Proteobacteria. Coarse fractions (>1.5 mu m) mainly contained mineral-derived components (Mg2+, Ca2+) and carbonate carbon from natural sources, with greater microbial diversity dominated by Firmicutes (29 %) and Actinobacteriota (25 %). Key opportunistic pathogens (Acinetobacter, Staphylococcus, and Lactobacillus) and antibiotic resistance genes with tetW and sul1 were the most abundant, followed by blaTEM and intl1 were significantly more abundant in coarse fractions. Particle size, rather than seasonality, was found to primarily determine chemical composition and microbial community structure. Key genera (Acinetobacter, Delftia, Paucibacter, and Pseudomonas) positively correlated with anthropogenic chemicals but negatively with ARGs, while ARG-harboring genera associated strongly with mineral nutrients. These findings suggest coarse urban aerosols function as reservoirs of antibiotic resistance genes and opportunistic pathogens, with abundance peaking in warmer months, raising public health concerns through inhalation exposure.
Keywords: Bioaerosols; Urban air quality; Airborne bacterial communities, Temporal dynamics; Particle size segregation